Death of a generation : how the assassinations of diem and jfk prolonged the vietnam war. - Jones, Howard, 1940- (Oxford Univ Press, 2003)
The assassination of John F. Kennedy led to the "death of a generation". The president had planned to withdraw all special forces by the end of 1965. But White House involvement in the Coup undercut the withdrawal effort and ultimately led to the war that Kennedy had sought to prevent.